2017
DOI: 10.1007/s12149-017-1183-2
|View full text |Cite
|
Sign up to set email alerts
|

18F-fluorothymidine PET imaging in gliomas: an update

Abstract: Brain neoplasms constitute a group of tumors with discrete differentiation grades, and therefore, course of disease and prognosis. Magnetic resonance imaging (MRI) remains the gold standard method for the investigation of central nervous system tumors. However, MRI suffers certain limitations, especially if radiation therapy or chemotherapy has been previously applied. On the other hand, given the development of newer radiopharmaceuticals, positron emission tomography (PET) aims to a better investigation of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 60 publications
0
21
0
1
Order By: Relevance
“…[ 18 F]FLT has been extensively used in the field of oncology to characterize tumors and predict the response to personalized therapeutic approaches ( Schelhaas et al, 2017 ). Therefore, the main application of this radiotracer in neurology has been restricted to the diagnosis of glioblastoma ( Nikaki et al, 2017 ; Brahm et al, 2018 ). Nevertheless, few studies have reported the visualization of endogenous neural stem cells in living animals using [ 18 F]FLT after focal cerebral ischemia, that could be used to monitor the effect of drugs aimed at expanding the neural stem cell niche ( Rueger et al, 2010 , 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 F]FLT has been extensively used in the field of oncology to characterize tumors and predict the response to personalized therapeutic approaches ( Schelhaas et al, 2017 ). Therefore, the main application of this radiotracer in neurology has been restricted to the diagnosis of glioblastoma ( Nikaki et al, 2017 ; Brahm et al, 2018 ). Nevertheless, few studies have reported the visualization of endogenous neural stem cells in living animals using [ 18 F]FLT after focal cerebral ischemia, that could be used to monitor the effect of drugs aimed at expanding the neural stem cell niche ( Rueger et al, 2010 , 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…18 F-FLT transport is mediated mainly by active Na + -dependent carriers through nucleoside transporters (salvage thymidine pathway) but also by passive diffusion. Similarly to what happens with 18 F-FDG, the tracer is subsequently trapped into the cell thanks to the phosphorylation by thymidine kinase-1 (TK-1) into 18 F-FLT monophosphate which is not incorporated into the DNA chains; TK 1 activity is almost absent in non-replicating cells, whereas its activity reaches the maximum in the late G 1 and S phases of the cell cycle in proliferating cells, thus reflecting tumor proliferation [58]. However, with respect to brain tumors, newer evidence suggests that 18 F-FLT uptake could be also associated with non-specific leakage, thus probably representing BBB breakdown and reflecting an increased permeability, whereas the contribution of the metabolic trapping through TK1 activity seems to be less important.…”
Section: F-fltmentioning
confidence: 99%
“…Whereas the sensitivity of FLT PET for detecting high-grade gliomas can reach 100%, a lower overall sensitivity of 83% has been shown because of major differences in uptake between high- and low-grade tumors [ 72 73 ]. Hence, the sensitivity of all grades is typically lower than with FDG PET [ 74 ] and methionine PET [ 75 ].…”
Section: Flt Petmentioning
confidence: 99%